Plantains thrive better with perennial cultivation - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
A decade-long research programme has shown that plantains grow best in a multispecies alley cropping system, with the crop being cultivated on a perennial system. Early in the 1980s researchers at the International Institute of Tropical Agriculture...